A homogenisation scheme for ultrasonic Lamb wave dispersion in textile composites through multiscale wave and finite element modelling. Issue 6 (30th March 2021) - Thierry, V.; Cantero‐Chinchilla, S.; Wu, W.; Lhemery, A.; Chronopoulos, D.
Summary: In this work, homogenisation of textile composite models is studied in order to increase the accuracy of wave dispersion predictions in such complex structures. A multiscale methodology is formed involving (i) calculation of the ultrasonic wave propagation through a detailed mesoscale finite element model of the textile and (ii) updating the mechanical properties of a semi‐analytical finite element (SAFE) model to match the accurate mesoscale predictions. The speeds of the first shear ( S H 0 ) and Lamb wave modes ( A 0 and S 0 ) are used to define the objective function to minimise in an inversion process based on genetic algorithms. The algorithm is tested on an orthotropic plate structure whose all nine unknown elastic moduli are successfully reconstructed and is then applied to three different numerical models. We demonstrate both numerically and experimentally that the proposed scheme provides more accurate dispersion characteristics compared to the ones obtained through the statically measured mechanical properties.